Outcome and Causes of Acute Renal Failure in Women during Peripartum Period - Awan, Shazia; Dars, Saira; Junejo, Saima; Rani, Shazia; Sikandar, Raheel (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To find the causes of occurrence and outcome of acute renal failure in women during peripartum period. METHODOLOGY: This prospective study was conducted in department of Gynae & Obsts. in collaboration with urology department at Liaquat University of Medical & Health Sciences Jamshoro from February 2015 to January 2017. Sample size was 90, overwhelming patients coming from peripheral area. Data was analyzed in SPSS version 21.0. Mean and standard deviation for quantitative variables such as age, gravidity & parity, frequency and percentages were calculated for qualitative variables; pre-eclampsia, eclampsia, hemolysis, post and antepartum hemorrhages, high liver enzymes, puerperal sepsis, low platelets, disseminated intravascular coagulation and outcomes like complete, partial and non-recovery. T-test was applied to evaluate the causes and outcomes. P value (P < 0.05) was considered as significant. RESULTS: Causes of 90 patients, which includes pre-eclampsia, eclampsia 11(12.22%), Postpartum hemorrhage 9(10%), Ante-partum hemorrhage 10(11.11%), 27 (30%) Hemorrhage, HELLP Syndrome 3 (3.33%), purpeural sepsis and disseminated intravascular coagulation 7(7.77%), Ruptured Uterus 4 (4.44%), hemolysis, elevated liver enzyme and Low Platelets Syndrome 5(5.55%), disseminated intravascular coagulation 4(4.44%), Dehydration 4(4.44%) and Obstructed Labor 6(6.66%). Outcome of acute renal failure in women during peripartum period, includes maternal outcome, delayed complete recovery, partial recovery, non-recovery, referred for dialysis. CONCLUSION: We concluded that the frequently causes were peripartum haemorrhage, eclampsia pre-eclampsia, puerperal sepsis and these sources were risk factors to increase morbidity and mortality.